Conditions and Guidelines of Learning Organization in Educational Institutions Under Phitsanulok Provincial Administrative Organization - Tunta, Malaipim; Pooncharoen, Nattachet (Journal of Graduate MCU KhonKaen Campus, 2024)
The purposes of this research were 1) to study the condition of learning organization in educational institutions under Phitsanulok Provincial Administrative Organization 2) to study the guidelines of learning organization in educational institutions under Phitsanulok Provincial Administrative Organization. This research was conducted using the following two phases according to the research objectives: Phase 1: Studying the condition of learning organization in educational institutions under Phitsanulok Provincial Administrative Organization: In order to study the condition of learning organization in educational institutions, the questionnaire based on Marquardt model were conducted with 105 teachers and education personnel from Phitsanulok Provincial Administrative Organization. The statistics used in data analysis were frequency, percentage, arithmetic mean, and standard deviation. Phase 2: Studying the guidelines of learning organization in educational institutions under Phitsanulok Provincial Administrative Organization. The research instruments consisted of a semi-structured interview in 5 areas: 1) learning dynamics 2) organizational change 3) people empowerment 4) knowledge management and 5) technology application. Content analysis was used to analyze results from studying the guidelines of learning organization in educational institutions from semi-structured interviews. The research results revealed that 1) the condition of learning organization in educational institutions under Phitsanulok Provincial Administrative Organization overall and each aspect were at a high level. 2) the guidelines of learning organization in educational institutions under Phitsanulok Provincial Administrative Organization consisted of setting specific, mission, and goals, Applying new skills and methods Create continuous learning at all levels Decentralize power, granting authority according to roles and responsibilities. according to knowledge and ability, Focusing on participatory work, Using encouraging technology to develop information systems to information, Encourage teachers and personnel to use technology to create learning management innovat and supportive and encouraging teachers to have higher academic status, to benefit the effective development of education.